Sickle cell-induced ischemic priapism - Salma AlDallal; Nasser AlDallal; Adel Alam (Cogent Medicine, 2016)
Priapism is one of the complications of Sickle cell disease (SCD). Priapism can be classified into ischemic (low-flow), non-ischemic (high-flow), or recurrent (stuttering). Ischemic priapism affects up to half of all men with SCD. Therefore, education coupled with more research on treatment options may help the patients with SCD to avoid the social, psychological, and medical implications of this condition and its embarrassing complications. This paper will focus on the mechanisms underlying the development of ischemic priapism in SCD, current preventative treatment strategies, and future directions for improved management of this condition.